The “Soft Skills” of plastic surgeons and their teams, compared to other occupations in a COVID-19 pandemic environment - Marco Flávio Mastrandonakis; Amilton Braio Ara; Ana Cristina Limongi França; Eder de Carvalho Januário; Manuela Brandão Borges; Thiago Schiavon Ara; Andressa de Fátima Kotleski Thomaz-de-Lima (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: This article aims to understand the importance of “Soft Skills “digital recruitment and selection. The term “Soft Skills” means psychological attitudes and constructive behaviors in interacting with people and groups. In this context, the tools used to evaluate them and the appropriate Soft Skills in the various professional areas during COVID-19 were identified. Methods: The primary data collection was carried out through interviews with experts in April 2020, and a survey applied between July and December 2020. After cleaning the data, the sample resulted in 169 respondents, allowing the performing descriptive statistical analysis of the data. Results: It was observed that Soft Skills have become more strategic in COVID-19. In addition, when comparing physicians specializing in Plastic Surgery with other professions, there was a higher incidence of the degree of total agreement among plastic surgeons. Conclusion: The results found may suggest that the strategic importance of Soft Skills has become even more intense among physicians specializing in Plastic Surgery. These results, obtained through a survey with quantitative data, align with this article’s scientific literature and with corporate organizations’ studies.